The Influence of Effort and Performance Expectancy on Employees to adopt e-Government: evidence from Oman - Alraja, Mansour Naser; Hammami, Samir; Chikhi, Billal; Fekir, Samia (International Review of Management and Marketing, 2016)
In the same context of previous studies on the adoption of e-government, this paper employs the Unified Theory of Acceptance and Use of Technology (UTAUT) model two constructs from this model were selected (Performance Expectancy, and Effort Expectancy) to examine their effect on the intention to adopt electronic government in Sultanate of Oman from an employees’ perspective. A manual survey was conducted to collect the request data. The total number of valid questionnaires for analysis was 204 which formed (83.3 %) of the study sample. To confirm the internal consistency of construct and measures validity, Factor analysis and Reliability test were used for this purpose. In addition to, the multiple linear regression was used to test the study hypotheses. The study model explained (50.5 %) of the whole deviation in employees’ Intention to adopt e-government. Moreover, both constructs Performance Expectancy, and Effort Expectancy have a significant influence on employees’ intention to adopt the electronic government. To empower employees to response to the requested e-services by citizens or businesses in real time, the adopted system to provide e-government services must be simplified, in addition to equipping employees with needed skills to use the mentioned system. The study originality lies in narrowing the UTUAT model which adopted only two constructs (Performance Expectancy, and Effort Expectancy) of this model. Then, implementing this adopted model on employees as individuals, not as representatives of government institutions, which considered the first study attempted to do such investigation. Keywords: Effort Expectancy, Performance Expectancy, UTAUT, e-government, Employees. JEL Classifications: C2, H11